Reproducibility and Reuse of Adaptive Immune Receptor Repertoire Data - Breden, Felix; Luning Prak, Eline T.; Peters, Bjoern; Rubelt, Florian; Schramm, Chaim A.; Busse, Christian E.; Vander Heiden, Jason A.; Christley, Scott; Bukhari, Syed Ahmad Chan; Thorogood, Adrian; Matsen IV, Frederick A.; Wine, Yariv; et al. (Frontiers in Immunology, 2017)
High-throughput sequencing (HTS) of immunoglobulin (B-cell receptor, antibody) and T-cell receptor repertoires has increased dramatically since the technique was introduced in 2009 [1-3]. This experimental approach explores the maturation of the adaptive immune system and its response to antigens, pathogens and disease conditions in exquisite detail. It holds significant promise for diagnostic and therapy-guiding applications. New technology often spreads rapidly, sometimes more rapidly than the understanding of how to make the products of that technology reliable, reproducible or usable by others. As complex technologies have developed, scientific communities have come together to adopt common standards, protocols and policies for generating and sharing data sets, such as the MIAME protocols developed for microarray experiments. The Adaptive Immune Receptor Repertoire (AIRR) Community formed in 2015 to address similar issues for HTS data of immune repertoires. The purpose of this Perspective is to provide an overview of the AIRR Community’s founding principles and present the progress that the AIRR Community has made in developing standards of practice and data sharing protocols. Finally, and most important, we invite all interested parties to join this effort to facilitate sharing and use of these powerful data sets (join@airr-community.org).